2018
DOI: 10.1177/0003489418790284
|View full text |Cite
|
Sign up to set email alerts
|

Early Indication of Noise-Induced Hearing Loss in Young Adult Users of Personal Listening Devices

Abstract: These findings suggest that preventive measures may be warranted to prevent a future increase of clinically relevant NIHL among heavy users of PLDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 33 publications
(45 reference statements)
0
24
0
2
Order By: Relevance
“…The overall effect size of the DPOAEs was 0.089 (CI −0.012 to 0.190; p 0.080, I 2 0%), indicating no significant amplitude change within 24 h after music exposure. In sum, the short-term result after music exposure did not show any meaningful changes for PTA thresholds or DPOAE amplitudes To identify the long-term hearing changes after music exposure [9,21,22,24,26,30,31,33,34], the pooled studies for analysis are shown in Figures 4 and 5 for PTA and DPOAE, respectively, in the same frequencies along with the short-term hearing changes. Similar to PTA outputs, the amplitude of DPOAEs showed the largest effect size also at 4 kHz (0.124, CI −0.047 to 0.296; p 0.155) (see Figure 3).…”
Section: Meta-analysis Of Music Exposure Effects With Subgroup Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…The overall effect size of the DPOAEs was 0.089 (CI −0.012 to 0.190; p 0.080, I 2 0%), indicating no significant amplitude change within 24 h after music exposure. In sum, the short-term result after music exposure did not show any meaningful changes for PTA thresholds or DPOAE amplitudes To identify the long-term hearing changes after music exposure [9,21,22,24,26,30,31,33,34], the pooled studies for analysis are shown in Figures 4 and 5 for PTA and DPOAE, respectively, in the same frequencies along with the short-term hearing changes. Similar to PTA outputs, the amplitude of DPOAEs showed the largest effect size also at 4 kHz (0.124, CI −0.047 to 0.296; p 0.155) (see Figure 3).…”
Section: Meta-analysis Of Music Exposure Effects With Subgroup Analysismentioning
confidence: 99%
“…The authors confirmed that four [9,[20][21][22] of the selected studies had "good" quality (scored 7-9). The remaining studies were evaluated as having "fair" quality (score 4-6) [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] except for one study with a score of 3, evaluated as having "poor" quality [35]. Thus, 16 articles were included for systematic review and meta-analysis in this study.…”
Section: Selection Outcomesmentioning
confidence: 99%
See 3 more Smart Citations